Pengaruh Talent Management Dan Job Insecurity Terhadap Produktivitas Kerja Karyawan Ninja Ekspress Kota Tasikmalaya - Randy Kurniadji Lubis; Barin Barlian; Dudu Risana (Jurnal Multidisiplin Dehasen (MUDE), 2024)
This research aims to determine the influence of Talent Management and Job Insecurity on work productivity (survey of Ninja Ekspress employees in Tasikmalaya City). The method used in this research is causality through a survey approach. This research is quantitative research using the causality method with a survey approach. The sample in this research was 74 Ninja Ekspress warehouse employees. The analytical tool used in this research is multiple regression using SPSS 26.0. The research results show that Talent Management, Job Insecurity and Work Productivity of Tasikmalaya City Ninja Express Employees have a very good assessment classification. Talent Management and Job Insecurity simultaneously have a significant effect on the Work Productivity of Tasikmalaya City Ninja Express Employees. Talent Management partially has a significant effect on the work productivity of Ninja Ekspress employees in Tasikmalaya City. Job Insecurity partially has a significant effect on the Work Productivity of Tasikmalaya City Ninja Express Employees.